Water Transportation in Bangkok: Past, Present, and the Future - Hossain, Moinul; Iamtrakul, Pawinee (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Once, Bangkok was known to the world as the “Venice of the East.” However, the role of water based transport has diminished gradually over the last few decades and has vastly been replaced by traditional land-based transportation system. Nowadays, most of the waterway networks have been paved over with roads and the existing water transport facilities along the Chao Phraya river and its canals in Bangkok. Moreover, the existing system lacks adequate accessibility, inter-modal linkages as well as safety. This research study intends to present an overview of this public transport system together with its role and characteristics. In addition, it also intends to recommend some measures to improve the transportation system along these canals in Bangkok and exhibits how the reincarnation of this mode of transport can leave the urban transportation planners with substantial alternatives to provide mobility when traffic congestion and safety issues still remain unsolved in Bangkok. The study provides insight to incorporate water transport within the mainstream of transportation planning and progress towards a sustainable integrate transportation system which can alleviate the existing congestion and safety problems and eventually pacify the transformation of Bangkok from the “Venice of East” towards the “Jungle of Concrete.”